Does electronic data collection perform better than paper-based data collection in health research fieldwork? A participatory action research in Zanzibar - Ving Fai Chan; Fatma Omar; Eden Mashayo; Ai Chee Yong; Christine Graham; Ronnie Graham; Omar Juma Othman; Jamison Jones; Kajal Shah (BMJ Public Health)
Introduction Technological advancement in low-resource settings is opening the gateway to implementation of electronic data collection methods that improve data quality. We examined the concerns to use electronic data collection tool in Zanzibar, codeveloped a tool that addressed the concerns and evaluated the process and limitations of incorporating an electronic data collection tool aside from paper-based during a community-based study in Zanzibar.Methods The science of improvement Plan-Do-Study-Act model guided this mixed-method participatory action research (PAR). From November 2022 to October 2023, 14 data collection team members participated in (1) a consultative workshop with a fishbone analysis to understand their hesitance to use electronic data collection tools for fieldwork (Plan); (2) developing implementation and evaluation plan for the paper-based method (Do); (3) assessing the proportion of errors and challenges faced using paper-based method (Study); and (4) codeveloping, implementing and assessing an electronic data collection tool (Act).Results Stakeholders were hesitant to use electronic data collection tools because of fear of lost data due to poor internet, insufficient competency with technology due to lack of training, unfamiliarity with technology in general and fear of lost wages. The study revealed that using a paper-based data collection tool during baseline was time-consuming, with 12.8% of responses being errors (2611 errors out of 20 398 responses). However, once implemented, the electronic data collection application was fast and simple, with minimal errors (0.02%). Overall, there is a need to improve devices’ storage capacity devices and provide more training.Conclusion Using the PAR approach, we understood the concerns with electronic data collection tools, allowed the team to experience the challenges faced with the paper-based collection method, codeveloped an appropriate solution and changed their attitude towards using technology that could increase accuracy and efficiency of their fieldwork.